Peak Demand Management in Micro Hydro using Battery Bank - Paudel, Pradeep; Wasti, Shailesh (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
Millions of Nepali inhabit in a far-flung hamlet of Nepal, where the extension of national grid is unlikely even in the new future. Isolated Micro-hydro power plants are extensively used in these areas. This paper addresses the problem of deficient electricity during peak period in existing conventional micro-hydro plants by the introduction of battery storage in the plant. Micro-hydro plant with battery bank storages surplus power, which would be wasted in case of conventional micro-hydro plant, during off- peak period and supplies during peak period. The control strategies for Electronic Load Controller (ELC), three - phase ac/dc converter and buck converter are realized in Matlab Simulink environment. The simulated system was able to store surplus power into battery bank when load demand was less than power generated by Synchronous Generator (SG) and supply when the load demand was higher than generator’s generation. This model can be implemented in the already existing micro-hydro plants where the load demand for a short time has increased beyond generation capacity of generator. HYDRO Nepal JournalJournal of Water Energy and EnvironmentIssue No: 22Page: 34-40Uploaded date: January 14, 2018